Application of 25G vitreous cavity perfusion in phacoemulsification for cataract after vitrectomy - Xiao-Hua Zhao (Guoji Yanke Zazhi, 2016)
AIM: To explore the application of 25G vitreous cavity perfusion in phacoemulsification for cataract after vitrectomy. METHODS: Forty-eight patients(50 eyes)with cataract after pars planavitrectomy in our hospital from September 2013 to September 2014 were selected to receive phacoemulsification and implantation of artificial lens with 25G vitreous cavity perfusion. Best corrected visual acuity(BCVA), intraocular pressure(IOP), postoperative discomfort, healing of scleral puncture and postoperative complications were observed. RESULTS: All patients underwent surgery successfully. Compared to before operation, there was less patients with BCVA ≤0.1, more patients with BCVA 0.3-0.5, >0.5, >0.3(P<0.05). The visual acuity of 1 eye decreased because of vitreous hemorrhage caused by original fundus lesion recurrence. The mean IOP before operation and at 1, 7d, 6mo after operation were 14.67±0.62mmHg, 14.75±0.56mmHg, 14.86±0.58mmHg, 14.88±0.59mmHg, respectively. There were no statistically significant differences of IOP between that before operation and those at 1, 7d, 6mo after operation(P>0.05). No obvious eye discomfort and severe complications after operation were observed. CONCLUSION: The effect of 25G vitreous cavity perfusion in phacoemulsification for cataract after vitrectomy is good and it can maintain IOP, keep anterior chamber stable and decrease the complications risk.